Futsal court management system - Wan Ainur Afeeqa, Wan Azmi (2012)
Futsal Court Management System(FCMS)is developed to give an efficient system to the Chendering Futsal Court management. In the existing system,customer needs to come to the futsal court to make a booking.However,by using FCMS,they can make the online booking anywhere and anytime.This system is covering online booking for customer and online system for staff.This system is for the customers to booking court and other resources, view court availability via online system. Besides that,by using GSM modem,a confirmation message will be sent to customer’s mobile after they made the online booking. Based on the existing system, all the booking data, equipment data,staff profile and others will be stored manually in a log book.This is dangerous because the probability the data will be lost or damage is high.So, Futsal Court Management System is also developed for all the booking and management data can be stored in database which will be more secure.